Comparable foraging effort and habitat use between two geographically proximate tropical seabird colonies - Alice M. Trevail; Sonia Vallocchia; Malcolm A. C. Nicoll; Peter Carr; Stephen C. Votier; Hannah Wood; Robin Freeman (Marine Biology, 2024)
Effective seabird conservation requires understanding their marine spatial ecology. Tracking can reveal details of their foraging ecology and habitat use, as well as the suitability of marine protected areas for at-sea conservation, but results are often regionally specific. Here we characterised the foraging behaviour of tropical breeding brown boobies Sula leucogaster in the Chagos Archipelago, Western Indian Ocean, and tested habitat requirements. GPS tracking of thirteen individuals from two colonies, located 142 km apart on the same atoll (Great Chagos Bank), showed similar foraging effort and habitat preferences despite differences in season and breeding stage. Brown boobies from both tracked populations foraged close to the colony along the atoll shelf edge, avoiding deep oceanic areas and shallow waters of the Great Chagos Bank atoll, but within the Chagos Archipelago Marine Protected Area. Sea-level height anomaly and sea surface temperature were important foraging predictors at both sites, although birds experienced distinct environmental conditions between colonies. These results suggest that while brown boobies have colony-specific at-sea foraging areas, similarities in habitat drivers of distribution and foraging behaviour can inform predictions of distributions at other colonies within the archipelago, with important benefits for at-sea conservation efforts.